Hinduism: past and present - Michaels, Axel (Princeton University Press, 2004)
Theoretical and historical foundations. 1. Theoretical foundations -- Is India different? -- The identificatory habitus -- What is Hinduism? -- Hinduism and Hindu-ness -- Religion and Dharma -- Hindu religions and Hindu religiosity -- Great and little Hinduism -- Continuity and change -- 2. Historical foundations -- Epochs in the history of religions -- First epoch : Prevedic religions -- Second epoch : Vedic religion -- Third epoch : ascetic reformism -- Fourth epoch : classical Hinduism -- Fifth epoch : sects of Hinduism -- Sixth epoch : modern Hinduism -- Religious literature -- Vedic literature -- The literature of the ascetic reformation -- The literature of classical Hinduism -- The literatures of the Hindu sects -- Literatures of modern Hinduism.